Food Law and Regulation for Non-Lawyers : A US Perspective - C. Sanchez, Marc (Food Science Text Series,, 2015)
The book offers a succinct overview of key topics and core concepts for food scientists, quality managers, and others who need to understand the regulation of food and dietary supplements in the U.S. It was designed and modeled after a six-week introduction to food law course currently taught at Northeastern University, and serves as a practical tool for regulatory professionals. The book includes a chapter on each major topic, with summations of the legislative history and general legal landscape. Each chapter focuses the reader on major and emerging issues encountered by facilities. A comparative law section at the end of every chapter offers readers an ability to view alternative methods of regulation and enforcement. This design is unique and allows students and working professionals alike to understand core concepts and the practical application of the law to their work. Using a modified casebook method approach, the book also serves as a practical tool for regulatory professionals.